Monitoring of Ammoniacal Nitrogen and Phosphate in the Leachates When Diluted Palm Oil Mill Effluent was Used as a Fertilizer - Salleh, Nurul Iylia; Phan, Tze-Pei; Lau, Seng; Yeoh, Chee-Bee; Tay, Meng-Guan (Borneo Journal of Resource Science and Technology, 2019)
Palm oil mill effluent (POME) contains a high amount of nutrients and organic matter; therefore, it has been considered as an alternative liquid fertilizer (LF). However, the studies on the reuse of POME as fertilizer have been mostly limited to nutrients absorption but the leachates were neglected. Such approach caused potential impacts on ground water pollution. Thus, this research aimed to compare the leachabilities of ammoniacal nitrogen (NH3-N) and phosphate (PO43-), as well as the growth rates of oil palm seedlings in three different watering conditions. Six oil palm seedlings were watered with either POME, LF or tap water. The leachates from each seedling pot were collected weekly and analyzed for their NH3-N and PO43- concentrations. The pots which were watered with tap water showed the highest leaching rate of 0.0251 mg.L-1.week-1 for NH3-N and 0.0392 mg.L-1.week-1 for PO43-. The average concentrations of NH3-N in the leachates from the POME, LF and tap water potswere 0.45, 0.38 and 0.36 mg/L, respectively, whereas for PO43-, the average concentrations were 1.09 (POME), 0.96 (LF) and 0.66 (tap water) mg/L. The quickest plant growth rates were recorded in tap water (0.56 cm/day), followed by LF (0.51 cm/day) and POME (0.42 cm/day).